Pendekatan One Health Dalam Transmisi Lepra: Analisis Peran Manusia, Lingkungan, Dan Reservoir Hewan - Suriyani Tan; Sisca Sisca; Yani Kurniawan; Monica Dwi Hartanti; Triasti Khusfiani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Leprosy, commonly referred to as Hansen’s disease,remains a significant public health problem in several developing countries, including Indonesia, despite the widespread implementation of multidrug therapy (MDT). Conventional transmission models that primarily emphasize human-to-human contact are insufficient to fully explain the complex epidemiological patterns observed in endemic regions, such as persistent clustering and cases without known contact history. This study aims to comprehensively review current scientific evidence on leprosy transmission from a One Health perspective by integrating human, environmental, and animal factors. A literature review approach was conducted by searching scientific databases, including PubMed, Scopus, and Web of Science, for articles published between 2010 and 2025. Relevant studies were analyzed using a thematic approach based on the main components of One Health. The findings indicate that, in addition to human-to-human transmission, Mycobacterium leprae may persist in environmental reservoirs such as soil and water, and zoonotic transmission has been confirmed in certain regions. inang factors, including immune response, socioeconomic conditions, and living density, also play a critical role in disease susceptibility. In Indonesia, the uneven distribution of cases and the limited number of studies addressing environmental and animal aspects highlight important research gaps. In conclusion, the One Health approach provides a more comprehensive framework for understanding leprosy transmission, and its integration into research and control strategies is essential to support more effective and sustainable elimination efforts.